2002
DOI: 10.1002/mds.10044
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral subthalamic nucleus stimulation and quality of life in advanced Parkinson's disease

Abstract: We examined the impact of the subthalamic nuclei (STN) deep brain stimulation (DBS) on the health-related quality of life (QoL) of patients with advanced Parkinson's disease (PD). Seventeen consecutive patients with refractory motor fluctuations and dyskinesia were included in the study (mean age, 60.9 +/- 7.7 years [range, 43-74 years]; disease duration, 16.4 +/- 8.5 years [range, 7-38 years]; mean off-medication Hoehn and Yahr stage, 4.23 +/- 0.66 [range, 2.5-5]). Each patient's assessment was carried out us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
91
3
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 26 publications
13
91
3
2
Order By: Relevance
“…Quality of life improves after STN DBS, 56,[63][64][65][66][67] and this improvement correlates with motor benefit. 65 In support of this finding, the physical markers for quality of life are reported to improve significantly, but other aspects such as mental, emotional well-being, social support, cognition, and communication show no improvement.…”
Section: Beneficial Effectmentioning
confidence: 92%
See 1 more Smart Citation
“…Quality of life improves after STN DBS, 56,[63][64][65][66][67] and this improvement correlates with motor benefit. 65 In support of this finding, the physical markers for quality of life are reported to improve significantly, but other aspects such as mental, emotional well-being, social support, cognition, and communication show no improvement.…”
Section: Beneficial Effectmentioning
confidence: 92%
“…65 In support of this finding, the physical markers for quality of life are reported to improve significantly, but other aspects such as mental, emotional well-being, social support, cognition, and communication show no improvement. 66,67 The improvement in quality of life is maintained over time. 64,65 The caregiver's quality of life can also improve.…”
Section: Beneficial Effectmentioning
confidence: 99%
“…In most patients, DBS alleviates parkinsonian motor signs, shortens 'off' periods, and reduces druginduced dyskinesias, dystonia, and motor fluctuations (Rodriguez-Oroz et al, 2004;Anderson et al, 2005;Weaver et al, 2005;Portman et al, 2006;Bronstein et al, 2011). In general, both GPi-and STN-DBS are more effective than medical management alone to alleviate motor deficits in patients with advanced PD (Just and Ostergaard, 2002;Martinez-Martin et al, 2002;Troster et al, 2003;Lezcano et al, 2004;Diamond and Jankovic, 2005;Erola et al, 2005;Halbig et al, 2005;Lyons and Pahwa, 2005;Deuschl et al, 2006;Rodrigues et al, 2007a, b;Montel and Bungener, 2009;Weaver et al, 2009b;Zahodne et al, 2009). In contrast to patients with GPi-DBS, those with STN-DBS are often able to substantially reduce the medication doses (Breit et al, 2004; …”
Section: Current Surgical Targetsmentioning
confidence: 99%
“…The calculated incidence of complications associated with laparoscopic bariatric surgery, obtained from the case series, 4,8,10,17,28,38,44,45,52,74,77,82,83,91,120 is summarized in Table 1; complications associated with DBS studies are shown in Table 2. 6,7,9,12,16,20,26,27,31,37,39,47,[55][56][57][58][59][60][61]64,[67][68][69]71,78,80,81,84,[86][87][88][89][96][97]…”
Section: Resultsmentioning
confidence: 99%